The Psychological Guidelines In Light Of The Quran And The Prophet's Sunnah - Nesreen mohammad Alqudah; Shumsudin Yabi; Kauthar Abd Kadir (NUNGEMILANG ENTERPRISE, 2024)
BITARA International Journal of Civilizational Studies and Human Sciences Volume 7 No.4 Page (210-219)